Peranan Dinas Pemberdayaan Perempuan dan Perlindungan Anak Kabupaten Madiun dalam Menekan Angka Pernikahan Dini - Ririn Aminarsih; Farid Pribadi (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2024)
Early marriage is a marriage between a prospective bride and groom who have not reached the age of 19 years. The Madiun Regency Population Control and Family Planning, Women's Protection and Child Protection Office is one of the footholds in reducing the number of child marriages in the Madiun Regency area. This study aims to determine the role of the Madiun Regency Population Control and Family Planning, Women's Protection and Child Protection Office in suppressing early marriage rates and what efforts are made to have a positive impact on reducing marriage rates in Madiun Regency. This research is a qualitative study from the perspective of Talcott Parsons' functional structural theory. The data collection techniques used are structured interviews with employees of the Women's Empowerment and Child Protection Division, observation, and documentation. The data analysis techniques used are data reduction, data presentation and conclusion drawing. The results of this study indicate that the role of the Madiun Regency Population Control and Family Planning, Women's Empowerment and Child Protection Office in reducing the number of early marriages with efforts including socialization to schools, establishing children's forums, and conducting MoUs with the Religious Court to facilitate premarital counseling as a condition for applying for marriage dispensation (Diska).